The rights of children to live in a family environment free from Gender Violence - Picontó Novales , Teresa (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
In the context of the rights of children in the family, child victims of gender violence have the right to live free of this violence. This article examines the legislative reforms in 2015 and 2021 and judicial praxis of shared custody, contact and communications orders in cases of gender violence in Spain. More specifically, the paper analyses the incompatibility of shared custody, contact and communications orders in cases of gender violence in the framework of these legal reforms.
Keywords: child victims of gender violence; shared custody contact and communications orders in cases of gender violence